Tonsillectomy associated with an increased risk of autoimmune diseases: A national cohort study. (August 2016) - Ji, Jianguang; Sundquist, Jan; Sundquist, Kristina
Abstract: Background: Tonsillectomy is a common surgical procedure. Recent evidence suggests that tonsils play an important role in our immune system. We thus hypothesize that individuals with tonsillectomy may face an increased incidence of autoimmune diseases in their later life. Methods: All individuals that had a tonsillectomy in Sweden between 1997 and 2012 were identified from the Swedish Hospital Discharge and Outpatient Register, and were followed until the diagnosis of a set of autoimmune diseases. Standardized incidence ratios (SIRs) were used to calculate the risk of autoimmune diseases as compared to the general population. Results: A total of 179, 875 individuals received a tonsillectomy in Sweden and 5357 of them were subsequently diagnosed with autoimmune diseases, giving an overall SIR of 1.34 (95%CI 1.30–1.37). For specific autoimmune diseases, 16 of them showed a significantly increased SIR, ranging between 1.21 and 2.97. The increased incidence was largely consistent irrespective of gender, age at operation, and underlying indications of tonsillectomy. Conclusions: The incidence of a group of autoimmune diseases was higher in individuals operated with a tonsillectomy. Immune dysfunction due to tonsillectomy may partly explain the observed association. However, the underlying mechanisms need to be explored in future studies. Highlights: The incidence of a group of autoimmune diseases was higher in individuals operated with a tonsillectomy. The increase was consistent irrespective of gender, age at operation, and underlying indications. Immune dysfunction due to tonsillectomy may partly explain the observed association.